2019
DOI: 10.1111/tbed.13125
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and phylogenetic analysis of porcine circovirus type 3 in 21 Provinces of China during 2015–2017

Abstract: Summary The emerging Porcine circovirus type 3 (PCV3) is associated with porcine dermatitis and nephropathy syndrome, reproductive failure and cardiac and multisystemic inflammation. To trace the prevalence and evolution of PCV3 in pigs with respiratory diseases or digestive diseases in China, 616 samples were collected from 21 provinces or municipalities of China from 2015 to 2017. All samples were analysed with PCR and a cap‐gene‐based phylogeny. The results indicated that the positive rate of PCV3 was 12.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 28 publications
10
65
5
1
Order By: Relevance
“…In contrast to the two previous studies evaluating such putative relationship (Qi et al, ; Zhai et al, ), no significant differences in terms of PCV‐3 DNA frequency detection were found among pigs with respiratory or digestive disorders compared between them or with age‐matched healthy animals. The previously mentioned studies referred to samples from China and used either serum (Zhai et al, ) as in the present work or intestinal/lung tissues (Qi et al, ), collected based exclusively in the animals showing clinical signs.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…In contrast to the two previous studies evaluating such putative relationship (Qi et al, ; Zhai et al, ), no significant differences in terms of PCV‐3 DNA frequency detection were found among pigs with respiratory or digestive disorders compared between them or with age‐matched healthy animals. The previously mentioned studies referred to samples from China and used either serum (Zhai et al, ) as in the present work or intestinal/lung tissues (Qi et al, ), collected based exclusively in the animals showing clinical signs.…”
Section: Discussioncontrasting
confidence: 97%
“…At the same time, PCV‐3 was detected in sows displaying reproductive problems, increased mortality rate, and suffering from respiratory disorders and porcine dermatitis and nephropathy syndrome (PDNS) (Palinski et al, ). Since the very first description of PCV‐3, this virus has been found in pigs with respiratory clinical signs and lung lesions (Kedkovid et al, ; Qi et al, ; Shen et al, ; Zhai et al, ), digestive disorders (Qi et al, ; Zhai et al, ), congenital tremors (Shen et al, ), rectal prolapse (Phan et al, ) and periweaning failure‐to‐thrive syndrome (Franzo, Kekarainen, Llorens, Correa‐Fiz, & Segalés, ). However, several of these studies where PCV‐3 was found in diseased animals failed to provide healthy age‐matched pigs as control groups (Kedkovid et al, ; Palinski et al, ; Phan et al, ; Shen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous reports, there are six variant sequences of amino acids 24 to 27 of the Cap . Several studies suggest that these four amino acids are associated with genetic variation and evolution of PCV3 (Ha et al, 2018;Qi et al, 2019). In addition, we also found mutations in other amino acids of the Cap (D124 to N124 and G160 to R160).…”
Section: Discussionsupporting
confidence: 63%
“…Subsequently, this virus has been detected in many countries and has an abnormally high positive rate (Costa et al, 2014;Deim et al, 2019;Faccini et al, 2017;Saraiva et al, 2019). In China, multiple epidemiological surveillance data indicated that this virus was extensively prevalent in pigs in many provinces and specific cities (Qi et al, 2019;Sun et al, 2018). Multiple studies have revealed that the virus was associated with several diseases (such as PDNS, multisystemic inflammation, reproductive failure) and coinfects with other viruses (for example, Torque teno sus virus, PCV2, porcine reproductive and respiratory syndrome virus) Ha et al, 2018;Wen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%